The Future of Smart Contracts in Indonesia’s Commercial and Business Law System - Leonardus Teguh Handoyo; Anggun Wida Prawira; Aswanto Aswanto (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
This research examines the future regulatory position of blockchain based smart contracts within Indonesia’s commercial and business law system by focusing on the unresolved legal tensions between conventional contract doctrine and decentralized digital governance. The study applies normative juridical and doctrinal legal research methods supported by statutory, conceptual, and comparative approaches to analyze the Indonesian Civil Code, Government Regulation Number 71 of 2019, Law Number 1 of 2024 concerning Electronic Information and Transactions, and Law Number 4 of 2023 concerning Financial Sector Development and Strengthening. The findings demonstrate that Indonesian contract law remains structurally dependent upon conventional assumptions concerning consent, enforceability, jurisdiction, evidentiary authority, and institutional dispute settlement, while blockchain based transactions increasingly operate through autonomous computational execution beyond traditional judicial intervention. Comparative analysis reveals that several jurisdictions have adopted technologically adaptive regulatory models integrating blockchain governance, legal sandbox mechanisms, digital commercial supervision, and hybrid dispute resolution frameworks. The research concludes that Indonesia requires comprehensive legislative reform capable of harmonizing commercial modernization, algorithmic governance, and legal certainty within the expanding architecture of decentralized digital commerce.